ANALOGIES AND DIFFERENCES BETWEEN THE GREAT DEPRESSION AND THE CURRENT REALITIES OF EMPLOYMENT AND UNEMPLOYMENT IN THE UNITED STATES - Serohina , N. (Theory and Practice of Public Administration, 2021)
On the basis of the methodology of sovereign governance, a retrospective analysis of the US national security was carried out during the Great Depression, in order to look in the context of the security of the Institutional Stability on the back of the new geopolitical victories and overwhelms. Meta statistic - on the basis of the current scientific development of the problems of the Great Depression of the United States in the context of sovereign governance and the practical implementation of the policy of national security, to establish analogies and ideas in the history of the Great Depression and of the history of the United States.With the help of the systematic method, a link has been established between the changes in the productivity of employment and the positive possibilities for the renewal of economic growth in the United States.Seeing that the skin once, if the level of wretchedness in the United States is growing too young, in Americans there is a panic attitude and fighting, that the “important part” of the Great Depression can turn around.The factor of the Great Depression, which nominated people, was established: the tendency of investing by companies and private persons in stocks, prices and collapse of the stock market of the American stock market has been widely expanded; the visibility of the mechanisms of social welfare. It stands to reason that the inheritance of the Great Depression in general was thrown by the serious wicks and became a real threat to the national security, the territorial integrity and sovereignty of the United States. To begin, an unprecedented level of unemployment and growth of uncommon occupation was brought about before the mass education of Americans.